2003
DOI: 10.1177/1363460703006002004
|View full text |Cite
|
Sign up to set email alerts
|

Girls Want Sex, Boys Want Love: Resisting Dominant Discourses of (Hetero) Sexuality

Abstract: Based on empirical research with 17-19 year olds, this article explores young people's understandings of themselves as sexual in relation to dominant discourse of (hetero)sexuality. It is concerned with providing empirical evidence of resistance in young people's constitution of their sexual subjectivities. The research findings suggest that young people generally draw upon dominant discourses of (hetero)sexuality in their talk about themselves as sexual. However some took up subject positions that involved mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
162
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(174 citation statements)
references
References 10 publications
8
162
1
3
Order By: Relevance
“…Similar to Allen (2003), Renold and Ringrose find that ruptures can be swiftly followed by reterritorialisation (often 'of other forms of dominance, differentiation and Otherization '; 2008, 332). The authors also find that the more sustained and multiple ruptures appear to occur mainly within narratives of fantasy -such as about those about imagined futures.…”
Section: Finding New Spaces For Further Theorisations Of Agencymentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to Allen (2003), Renold and Ringrose find that ruptures can be swiftly followed by reterritorialisation (often 'of other forms of dominance, differentiation and Otherization '; 2008, 332). The authors also find that the more sustained and multiple ruptures appear to occur mainly within narratives of fantasy -such as about those about imagined futures.…”
Section: Finding New Spaces For Further Theorisations Of Agencymentioning
confidence: 99%
“…A notable exception is a more recent paper by Renold and Ringrose, in which the authors use 'Deleuze and Guattari's powerful conceptual repertoire ' (2008, 313) to examine how the actions of girls and young women rupture the heterosexual matrix. In a smaller field of study examining young women's approaches to and experiences within sexual and intimate relationships -theorisations of agency used tend to be either underdeveloped (Jackson and Cram 2003;Stewart 1999) or situated within a framework (Allen 2003(Allen , 2008Holland et al 1998) which focuses on identifying behaviours as either resistant to or accommodating of traditional discourses (Maxwell 2007) or 'dominating forces' (Allen 2008, 575).…”
Section: Finding New Spaces For Further Theorisations Of Agencymentioning
confidence: 99%
See 2 more Smart Citations
“…Thus dominant cultural ideas of female sexuality and power relationships make it very difficult for women to negotiate safe sex. However, recent studies have shown that whilst hegemonic ideas of masculinities and femininities exist, and lead to gendered expectations of behaviour (Gevers et al 2012), reality for many young people is more complex (Allen 2003a, 2003b, Maxwell 2007, Devries and Free 2010. Young women express sexual desire, which is not always viewed negatively, and young men express desire for emotional closeness and having someone to talk to (Allen 2004, Forrest 2010.…”
Section: Introductionmentioning
confidence: 99%